Oxidative Degradation of Brilliant Green by Potassium Iodate in Acidic Medium: A Kinetic and Mechanistic Study - Bano, Shakila; Singh, Vineeta; Hashmi, Ayesha; Singh, Ashutosh; Kumar Singh, Ajaya (Asian Journal of Chemistry, 2022)
Brilliant green (BG), one of the triphenylmethane dyes, has been extensively applied and produced as a colorant for different industries like medical, paper/textile printing, food additive, cosmetics, etc. Dyes effluents discharged by these industries pose hazardous effects on environmental and human health via releasing toxic and carcinogenic contaminants during its deterioration. The present work evaluates kinetic and mechanistic aspects of oxidative degradation of brilliant green by iodate in acidic solution at 303 K. The influence of different factors such as concentration of various reactants (μ), free radicals, etc. has also been investigated to check feasibility of redox degradation for efficient, easy, low-cost and eco-friendly removal of brilliant green from aquatic medium. The experimental result shows a first-order rate dependence on [BG] and zero-order kinetics with respect to [KIO3]. The reaction showed positive fractional order dependence on the rate for [H+]. Variations in ionic strength of the medium and [Cl–] did not bring about any noticeable change on the rate of reaction. It was found that the reaction rate declined with the decrease in the dielectric constant (D) of the medium in the oxidation of brilliant green. Additionally, the process was carried out at different temperatures to estimate the activation parameters and also to find rate controlling stages of the process. Finally, an appropriate mechanism, a plausible with the experimental observations, also supported by UV-Vis spectra has been proposed.